Enhancing the localised corrosion resistance of 316L stainless steel via FBR-CVD chromising treatment. (17th February 2018) - Xiong, Jianyu; Manjaiah, Gopinatha; Fabijanic, Daniel; Forsyth, Maria; Tan, Mike Yongjun
ABSTRACT: The resistance of stainless steels to localised corrosion can be adversely affected by environmental and metallurgical heterogeneities existed in complex industrial infrastructures such as seawater desalination plants exposed to aggressive evnironments. It is therefore critical to enhance the localised corrosion resistance and understand the corrosion behaviour of stainless steels in complex and aggressive industrial environmental conditions. In this work, the localised corrosion resistance of chromised stainless steel 316L (SS316L) in simulated seawater desalination systems has been investigated by electrochemical and surface analytical techniques. It has been found that chromising processes have improved the localised corrosion resistance of SS316L by reducing its susceptibility to pitting, crevice, and welding zone corrosion in simulated seawater desalination environments. This increased corrosion resistance has been explained by electrochemical polarisation studies and surface analysis showing that the chromising treatment at 1050°C resulted in a continuous and stable chromium-enriched layer on the SS316L surface.